Quality of life of men with AIDS and the model of social determinants of health - Gilmara Holanda da Cunha; Maria Luciana Teles Fiuza; Elucir Gir; Priscila de Souza Aquino; Ana Karina Bezerra Pinheiro; Marli Teresinha Gimeniz Galvão (Universidade de São Paulo, 2015)
OBJECTIVE: to analyze the quality of life (QoL) of men with AIDS from the perspective of the model of social determinants of health (MSDH). METHOD: cross-sectional study conducted in an outpatient infectious diseases clinic from a Brazilian university hospital over the course of one year with a sample of 138 patients. A form based on the MSDH was used to collect sociodemographic data addressing individual, proximal, intermediate determinants and the influence of social networks together with an instrument used to assess the QoL of people with HIV/AIDS. The project was approved by the Institutional Review Board (Protocol No. 040.06.12). RESULTS: according to MSDH, most men with AIDS were between 30 and 49 years old (68.1%), mixed race (59.4%), heterosexual (46.4%), single (64.5%), Catholic (68.8%), had a bachelor's degree (39.2%), had no children (61.6%), and had a formal job (71.0%). The perception of QoL in the physical, level of independence, environment, and spirituality domains was intermediate, while QoL was perceived to be superior in the domains of psychological and social relationship. A perception of lower QoL was presented by homosexual (p=0.037) and married men (p=0.077), and those with income below one times the minimum wage (p=0.042). A perception of greater QoL was presented by those without a religion (p=0.005), living with a partner (p=0.049), and those who had a formal job (p=0.045). CONCLUSION: social determinants influence the QoL of men with AIDS.